2017
DOI: 10.1038/s41598-017-01708-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sex-dependent mtDNA transmission in freshwater mussels (Bivalvia: Unionida)

Abstract: Doubly uniparental inheritance (DUI) describes a mode of mtDNA transmission widespread in gonochoric freshwater mussels (Bivalvia: Palaeoheterodonta: Unionida). In this system, both femaleand male-transmitted mtDNAs, named F and M respectively, coexist in the same species. In unionids, DUI is strictly correlated to gonochorism and to the presence of the atypical open reading frames (ORFans) F-orf and M-orf, respectively inside F and M mtDNAs, which are hypothesized to participate in sex determination. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 65 publications
7
57
0
Order By: Relevance
“…As mentioned above, modifications to the cox2 gene is a particular feature often found in DUI species. In unionid mussels, the longest cox2 gene is found in the M mtDNA of Hyridella menziesii (1,380 bp) 22 and is the result of a 3′ extension, as in other DUI unionids 21 . Previous studies indicated an extra-mitochondrial localization of MCOX2 as well as a possible involvement of the protein in reproduction in freshwater mussels 23,24 , further supporting the link between gender and mtDNA transmission patterns.…”
Section: Intraspecific Divergences Genetic Distances Of Individual Gmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned above, modifications to the cox2 gene is a particular feature often found in DUI species. In unionid mussels, the longest cox2 gene is found in the M mtDNA of Hyridella menziesii (1,380 bp) 22 and is the result of a 3′ extension, as in other DUI unionids 21 . Previous studies indicated an extra-mitochondrial localization of MCOX2 as well as a possible involvement of the protein in reproduction in freshwater mussels 23,24 , further supporting the link between gender and mtDNA transmission patterns.…”
Section: Intraspecific Divergences Genetic Distances Of Individual Gmentioning
confidence: 96%
“…Only ORFs encoding proteins with at least one predicted transmembrane domain were retained, because all sex-specific mtORFans characterized to date in DUI species (i.e. those encoding F-ORF in females and M-ORF in males), except for one case, possess at least one transmembrane domain or helix (TMH) 7,8,22,40 . In both S. plana and L. balthica F mtDNAs, only two unassigned regions were susceptible to contain supernumerary ORFs of >150 bp, i.e.…”
Section: Intraspecific Divergences Genetic Distances Of Individual Gmentioning
confidence: 99%
“…These tools are particularly important owing to the fact that many species present hidden cryptic diversity (Froufe et al, 2016b;Pfeiffer et al, 2016). Additionally, nextgeneration sequencing is now allowing for quicker and less expensive robust phylogenies using methods like whole-transcriptome and whole-mitogenome analyses with a wide range of markers (Guerra et al, 2017;Lopes-Lima et al, 2017c). Furthermore, using reduced genome representations or snip analyses, it is now possible to get more information on the phylogeographic patterns of species and on the definition of conservation units (Catchen et al, 2017;Desalle & Amato, 2017).…”
Section: Research and Conservation Actions Needsmentioning
confidence: 99%
“…The M-type and F-type mitochondrial lineages show high levels of divergence within species of Unionida freshwater mussels and even distinct gene order arrangements (Fonseca et al 2016;Froufe et al 2016;Guerra et al 2017). The Margaritiferidae also exhibit a unique M-type and F-type gene order (Lopes-Lima, Fonseca, et al 2017).…”
mentioning
confidence: 99%